2021
DOI: 10.3390/foods10061331
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprotective Effects of Xanthohumol against the Carcinogenic Mycotoxin Aflatoxin B1

Abstract: The present study addresses the chemoprotective effects of xanthohumol (XN), a prenylated flavonoid found in the female inflorescences (hops) of the plant Humulus lupulus L., against the carcinogenic food contaminant aflatoxin B1 (AFB1). The chemical reactions of XN and its derivatives (isoxanthohumol (IXN), 8-prenylnaringenin (8-PN), and 6-prenylnaringenin (6-PN)) with the AFB1 metabolite, aflatoxin B1 exo-8,9-epoxide (AFBO), were investigated in silico, by calculating activation free energies (ΔG⧧) at the Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Polyphenols, secondary plant metabolites that include phenolic acids, tannins, coumarins, lignins, stilbenes, terpenes, and flavonoids, naturally offer plants protection against abiotic stresses, UV light, pathogens, parasites, and plant predators [ 77 ]. Xanthohumol, a prenylated flavonoid isolated from hops ( Humulus lupulus L.), was proven to have chemoprotective effects against the carcinogenic food contaminant aflatoxin B1 that is produced by the fungi Aspergillus flavus and Aspergillus parasiticus [ 78 ]. Its antimutagenic effect is based on preventing the DNA adduct formation and DNA damage induction.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols, secondary plant metabolites that include phenolic acids, tannins, coumarins, lignins, stilbenes, terpenes, and flavonoids, naturally offer plants protection against abiotic stresses, UV light, pathogens, parasites, and plant predators [ 77 ]. Xanthohumol, a prenylated flavonoid isolated from hops ( Humulus lupulus L.), was proven to have chemoprotective effects against the carcinogenic food contaminant aflatoxin B1 that is produced by the fungi Aspergillus flavus and Aspergillus parasiticus [ 78 ]. Its antimutagenic effect is based on preventing the DNA adduct formation and DNA damage induction.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, hops contain bitter acids, which represent a great portion of dry hop cones and are further divided into α-acids (humulones) and β-acids (lupulones) [ 10 ]. In addition, flavonoids (with the main representative xanthohumol (XH)) also form important hop compounds [ 11 ] that exhibit antimicrobial activities [ 10 , 12 , 13 ] and anticarcinogenic effects [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The chemoprotective effect of 579 was investigated in vitro in the metabolically competent HepG2 cell line. The results indicated that 579 could act as a scavenger of AFBO, preventing DNA adduct formation and DNA damage induction (Štern et al 2021 ). 579 impaired the PMA-driven migratory and invasive capacity of A549 cells by decreasing the level of MMP-9 expression and concomitantly increasing TIMP-1 protein expression, a specific blocker of PRO-MMP-9 activation.…”
Section: Prenylated Flavonoids With Anti-inflammatory Activitymentioning
confidence: 99%